Academic routs of affirmative action students: a case study in light of equity, race and participatory parity - Grisa, Gregório Durlo; Neves, Clarissa Eckert Baeta; Raizer, Leandro (Universidade Estadual de Campinas, 2019)
This paper investigates the trajectories of students of affirmative action policies in a Federal University, and seeks to analyze the reasons for different academic routes. The methodology is based on the case study analysis, using student survey applied to tree groups: evaded, retained and graduated. The results are debated considering the concepts of Rawls, equity, Guimarães, race, and Fraser, participatory parity. Material and social variables contribute to explain the different trajectories. The lack of time to study is pointed out as decisive by students with difficulties in their courses. Family support and work are critical to academic success. Gender and race are influential variables in academic success and failure